Związki zespołu cech kręgosłupa-miednicy i stóp dziewcząt i chłopców w wieku od 4 do 18 lat = Relationships in the Spine-Pelvis System and Feet in Girls and Boys Aged 4 to 18 Years - Mrozkowiak, Mirosław; Jazdończyk, Paulina (Journal of Education, Health and Sport, 2015)
Mrozkowiak Mirosław, Jazdończyk Paulina. Związki zespołu cech kręgosłupa-miednicy i stóp dziewcząt i chłopców w wieku od 4 do 18 lat = Relationships in the Spine-Pelvis System and Feet in Girls and Boys Aged 4 to 18 Years. Journal of Education, Health and Sport. 2015;5(7):226-250. ISSN 2391-8306. DOI 10.5281/zenodo.19950 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A226-250 https://pbn.nauka.gov.pl/works/583791 http://dx.doi.org/10.5281/zenodo.19950 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2015. Revised 05.07.2015. Accepted: 10.07.2015. Związki zespołu cech kręgosłupa-miednicy i stóp dziewcząt i chłopców w wieku od 4 do 18 lat Relationships in the Spine-Pelvis System and Feet in Girls and Boys Aged 4 to 18 Years Mirosław Mrozkowiak1, Paulina Jazdończyk2 1Bioergonsport, Nowa Biała, Płock e-mail: magmar54@interia.pl, www: http://wadypostawy.republika.pl 2Gabinet Fizjoterapii Leszno Wlkp. Słowa kluczowe: cechy kręgosłupa, tułowia i stóp. Streszczenie Celem podjętych badań jest próba określenia wzajemnych związków zespołu cech kręgosłupa-miednicy i stóp w populacji dziewcząt i chłopców w wieku od 4 do 18 lat obojga środowisk. Hipoteza: Najistotniejszy związek cech stóp i kręgosłupa-miednicy występuje z cechami strzałkowymi kręgosłupa, a kręgosłupa-miednicy ze szerokością stóp. Materiał i metoda. Badania pozwoliły zarejestrować 21895 obserwacji 104 parametrów miednicy – kręgosłupa i stóp. Do ich oceny wykorzystano zestaw do komputerowej oceny postawy ciała wykorzystujący zjawisko mory projekcyjnej. Wnioski: 1. Najczęściej istotny związek cech kręgosłupa-miednicy z cechami stóp zachodzi ze strzałkowymi cechami długościowymi kręgosłupa, rzadziej czołowymi i poprzecznymi. Najczęściej też cechy te wykazywały związek z: szerokością prawej i lewej stopy, kątem szpotawości V palca prawej stopy, 2. Najczęściej istotny związek cech stóp z cechami kręgosłupa-miednicy zachodzi z szerokością obu stóp. Najczęściej też cechy te wykazywały związek z: wysokością i długością lordozy lędźwiowej oraz kifozy piersiowej, kątem nachylenia odcinka piersiowego górnego. Keywords: characteristics of the spinal column, body trunk and feet. Abstract The aim of the study is to attempt to determine mutual relationships between the characteristics of the spine-pelvis system and feet in the populations of girls and boys aged 4 to 18 years from two environments. Material and Method. During the examinations carried out among volunteers, the authors recorded 21895 observations of 104 parameters of the spine-pelvis system and feet in different age. In order to assess these parameters, the authors used a set for computer analysis of body posture based on a phenomenon of projection moiré. Conclusions. 1. The significant relationships between the characteristics of the spine-pelvis system and characteristics of feet occur the most often with sagittal length characteristics of the spine rather than those frontal or transverse. These characteristic showed the most frequently a relationship with the width of the right and left feet, angle of the hallux varus in right foot, 2. The significant relationships between the characteristics of feet with the characteristics of the spine-pelvis system occur the most often with the width of both feet. These characteristics showed the most frequently a relationship with the height and length of lumbar lordosis and thoracic kyphosis, inclination of the upper thoracic region.